The Life And The Scientific Heritage Of Mirza Sami - Hojiyevich, Turayev Halim; Bozorgul, Urinova Zokirovna; Azamatovna, Kalandarova Ferangiz (The journal of contemporary issues in business and government, 2021)
In the following article the info regarding the life and the scientific heritage of Mirza Muhammad Abdulazim Sami Bustani (1838-1907) who had been worked in as a munshi the end of the 19th century and the beginning of the 20th century, who had worked in the palace of the emir of Bukhara (Muzaffar), his books on the history of the emirate of Bukhara.